2020
DOI: 10.1016/j.hemonc.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of recombinant Human erythropoietin in neonatal anemia

Abstract: Aim: To estimate the blood level of Erythropoietin(EPO) in neonates with anemia of prematurity (APO) and in late hypo-regenerative anemia and to clarify role of EPO in correction of anemia and reducing the number of blood transfusions. Methods: This study was carried out on 60 neonates divided into; group I (30 preterm neonates) with AOP received EPO (250 IU/kg/dose subcutaneously 3 times weekly for 4 weeks), compared to group II (30 neonates) with AOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…Anemia of prematurity can cause tachycardia, inadequate weight gain, increase oxygen need and apnea or bradycardia (13,27,29). n premature infants, anemia becomes symptomatic when imbalance develops between it's distribution and consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia of prematurity can cause tachycardia, inadequate weight gain, increase oxygen need and apnea or bradycardia (13,27,29). n premature infants, anemia becomes symptomatic when imbalance develops between it's distribution and consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Además de estimular la eritropoyesis, inhibe la apoptosis en células vasculares y neuronas y regula la angiogénesis; su expresión depende de la presión arterial de oxígeno y está regulada por la hipoxia (40,41). El uso de eritropoyetina humana recombinante (rHu-EPO) como parte del tratamiento de la anemia del prematuro ha sido ampliamente discutido y controvertido, ya que la administración precoz de esta no reduce el número de transfusiones recibidas (5,41,42); sin embargo, hay estudios que demuestran una disminución en la necesidad de transfusiones sanguíneas (13,43,44).…”
Section: Administración Temprana De Agentes Estimulantes De La Eritropoyesisunclassified
“…Multiple studies have reported on the use of rEPO in extremely low gestational age neonates (ELGANs) to stimulate erythropoiesis and decrease the need for red blood cell transfusions. 4,[7][8][9][10][11][12][13][14] Previous trials have demonstrated that the administration of erythropoietin may reduce the need for future red blood cell transfusions, thereby reducing the risk of development of complications related to transfusion administration. 7,8 There is prospective data to both support and discourage the use of erythropoietin in preterm infants.…”
Section: Introductionmentioning
confidence: 99%